(untitled) - Packard, David (New YorkHarper, 1995)
From a one-car-garage company to a multibillion-dollar industry, the rise of Hewlett-Packard is an extraordinary tale of vision, innovation and hard work. Conceived in 1939, Hewlett-Packard earned success not only as a result of its engineering know-how and cutting-edge product ideas, but also because of the unique management style it developed -- a way of doing things called "the HP way".
Keywords: Ngành công nghiệp máy tính,Computer industry; Lịch sử,History; Hoa Kỳ,United States